A Brief Overview of Tauopathy: Causes, Consequences, and Therapeutic Strategies. (July 2017) - Orr, Miranda E.; Sullivan, A. Campbell; Frost, Bess
Abstract : There are currently no disease-modifying therapies for the treatment of tauopathies, a group of progressive neurodegenerative disorders that are pathologically defined by the presence of tau protein aggregates in the brain. Current challenges for the treatment of tauopathies include the inability to diagnose early and to confidently discriminate between distinct tauopathies in patients, alongside an incomplete understanding of the cellular mechanisms involved in pathogenic tau-induced neuronal death and dysfunction. In this review, we describe current diagnostic and therapeutic strategies, known drivers of pathogenic tau formation, recent contributions to our current mechanistic understanding of how pathogenic tau induces neuronal death, and potential diagnostic and therapeutic approaches. Trends: Current diagnostic strategies cannot detect prodromal tauopathy. Current therapeutic strategies for tauopathies are not disease modifying. Mutations in the tau gene, brain injuries, metabolic syndrome, mTOR hyperactivity, and spread from neighboring cells can stimulate formation of pathogenic tau. Pathogenic tau-induced alterations in genomic architecture cause neuronal death.